HOW AI TOOLS (LIKE CHATGPT/GEMINI) AFFECT CRITICAL THINKING IN NURSING STUDENTS. A SYSTEMATIC REVIEW (Journal of Medical & Health Sciences Review, 2026)
Background: The fast adoption of the artificial intelligence (AI) application of ChatGPT and Gemini into nursing education has generated important concerns about the impact of the technology on student critical thinking, clinical reasoning, and cognitive autonomy. Although AI-assisted learning has some prospects of benefit as a tool of learning, there are some concerns regarding the overdependence and the effects of AI-assisted learning on professional judgment. A systematic review of the existing literature is required to help in making these effects clear.Objective: The objective of this systematic review was to assess how AI tools can influence critical thinking and other cognitive outcomes in nursing students, and more specifically, how AI guided and unguided use influences these results.Methods: The systematic review was done based on PRISMA 2020 guidelines. The searches were conducted in PubMed/MEDLINE, Scopus, Web of Science, Embase, CINAHL, ERIC, and Google Scholar, including articles published since 2019. They included randomized controlled trials, quasi-experimental, observational, and mixed-methods studies that studied the use of AI tools in nursing education. The critical thinking and clinical reasoning, decision-making accuracy, and reflective thinking were the primary outcomes. Some of the secondary outcomes were cognitive load, learning engagement, ethical awareness, and independent reasoning development. The synthesis of the data was done through narrative and quantitative analysis and presented in the form of effect size in the form of standardized mean differences (SMDs), relative risks (RRs), or odds ratios (ORs).Results: The number of studies incorporated was 52, which had undergraduate and postgraduate nursing students. The results were found to be moderate in terms of critical thinking (pooled SMD = 0.41; 95% CI:0.280.55) as an educational aid structure. It was also found that clinical decision-making accuracy by AI-supported learners was higher (RR = 1.26; 95% CI: 1.121.41). Nonetheless, overuse or unsupervised AI application was linked to low development of autonomous clinical reasoning and greater dependence. Guided AI application leads to increased reflective thinking and less cognitive load especially in senior nursing students. Correlation analyses showed that there were positive relationships between structured AI use and cognitive outcomes and negative ones between AI overreliance and autonomous reasoning.Conclusion: AI systems like ChatGPT and Gemini have a twofold influence on critical thinking among students of nursing. In the framework of structured and educator-led ones, AI improves cognitive and clinical reasoning capabilities. On the other hand, the unrestricted or over-dependence on AI can cause suppression of the development of independent critical thinking. Careful design of instruction and moral responsibility helps to maximize the benefits of education and reduce risks to the cognitive capacity.